Factitious buccal lesion secondary to bruxism in a child with cerebral palsy. Issue 1 (22nd December 2005) - Harris, D
Abstract : Children with cerebral palsy are at greater risk of a whole range of oral conditions than their peers. These include bruxism (tooth grinding), oral skill dysfunction, gross malocclusion due to effects of the abnormal orofacial muscle tone on tooth eruption, drooling of saliva, and poor oral hygiene. 1 A challenging case of a painful buccal lesion in a 2 year old girl with cerebral palsy (CP) that did not respond to antifungal, antiviral or antibiotic treatment is presented as a factitious lesion. The recognition and significance of self-injurious behaviour and factitious lesions in children are discussed.